BRONCHOESOPHAGEAL FISTULA IN SHEEP – CASE REPORT - TACCANI, G. D. R.; SILVA, L. A.; LIMA, A. L. S.; OLIVEIRA, V. G.; SILVA, C. P. N.; CRUZ, R. S. F.; RIBEIRO, A. R. B.; CRESPILHO, A. M.; GUERRA, J. L.; CALEFI, A. S. (Ars Veterinaria, 2023)
The term bronchoesophageal fistula is used for the abnormal communication between the esophageal lumen and the pulmonary bronchi. There are no reports of this condition in production animals, and its origin is unknown. A male Dorper sheep from the Veterinary Hospital of the Santo Amaro University, SP, Brazil, presented clinical signs of tachypnea, apathy, and coughing after eating. The animal died suddenly after a fever break. During the gross evaluation, a fistula was noticed in the middle third of the thoracic esophagus with communication to the right cranial lung lobe, forming an encapsulated area measuring 24.5 cm x 22.0 cm x 9.4 cm. Fibrous tissue delimited the pulmonary lobe and feed filled the compartment. This is a rare condition with unclear etiopathogenesis.